BENEFITS IN THE DAILY LIFE OF HIGH HEALTH ACADEMY PRACTICERS – PI (Fiep Bulletin - online, 2017)
The present article deals with a quantitative research that aimed to verify the improvements of the functional capacitiesthrough the answers given as improvements in the daily activities of the practitioners. They were performed with 48 practitioners, where theresults were obtained that the great majority affirm to have obtained benefits in the daily life and improvements in the quality of life with thepractice of physical activity after their practice of physical activity in the Health Academy, therefore, concludes It is said that the benefitscited go beyond the physical in the life of these practitioners, have reported psychosocial benefits and improved quality of life ofpractitioners.